Philanthropic Foundations' Discourse and Nursing's Future: Part II: A Critical Discourse Analysis of RWJF Future of Nursing Initiatives. (6th April 2023) - Kneipp, Shawn M.; Canales, Mary K.; Drevdahl, Denise J.
Abstract : Critical social scholarship highlights the power philanthropic foundations wield on the collective agency of groups, yet analyses specific to nursing are absent in the literature. In this second of a 2-part series, we employed critical discourse analysis to examine how control of enunciative privilege in Robert Wood Johnson Foundation's (RWJF) 2010 and 2020-2030 Future of Nursing (FON) initiatives challenge nursing's ability to enact its collective agency, particularly through professional nursing organizations. Findings are discussed within the context of nursing's self-regulatory privileges, history, and agentic obligations that are bestowed on the discipline by the greater public for the public good.